Adsorption and Desorption of Na+ and NO3− Ions on Thermosensitive NIPAM-co-DMAAPS Gel in Aqueous Solution - Eva Oktavia Ningrum; Agus Purwanto; Eka Octaviyatna Mulyadi; Dinny Islamiah Dewitasari; Sumarno Sumarno (Universitas Gadjah Mada, 2017)
Adsorbent gel with the ability to absorb and to desorb Na+ and NO3− ions simultaneously with temperature swing was synthesized by free radical copolymerization reaction of N-isopropylacrylamide (NIPAM) and N,N-dimethyl-(acrylamidopropyl)ammonium propane sulfonate (DMAAPS). In this study, NIPAM acts as a thermosensitive agent and DMAAPS as an adsorbent agent. The purpose of this research is to investigate the effect of temperature and solution concentration on the swelling, adsorption, and desorption behaviors of NIPAM-co-DMAAPS gel. The relationship between adsorption and desorption behaviors of the gel was also elucidated. NaNO3 solution was selected as the target solution in swelling, adsorption, and desorption test. It was observed that the swelling degree of the gel increased as temperature and solution concentration raised. The adsorption amount of ions decreased with the increase of temperature. In contrast, the amount of ions desorbed from the gel increased linearly with temperature.